THE EFFECTIVENESS OF THE ORGANIZATION OF ANTITUBERCULOUS MEASURES IN THE POLTAVA REGION IN 2007 - 2011 YEARS - Yareshko, A.G.; Kulish, M.V.; Voroduhina, A.K.; Pecheritsa, V.G.; Пось, О.А. (World of Medicine and Biology, 2012)
To study the effectiveness of the organization of treatment of TB patients in the Poltava region in 2007 - 2011 years, we performed an analysis of statistical data on tuberculosis in the area during this period. The study showed that despite some improvement in the situation of TB in the Poltava region remains difficult. By the priority issues include lack of funding for the construction of in-patient department of the regional TB dispensary, which does not create separate departments for different group of patients with tuberculosis. Among other issues need to provide a dramatic increase in the number of patients with chemoresistant and HIV / AIDS-associated tuberculosis.
Keywords: tuberculosis; Poltava region; organization of treatment